Maximizing E-Tailers’ Sales Volume through the Shipping-Fee Discount and Product Recommendation System - Yan Guo; Xiaonan Hu; Yu Zou; Shouwei Li; Wenchuan Cheng; Zhiyong Li (Discrete Dynamics in Nature and Society)
E-tailers can impact customers’ order incidence and cart size by offering an attractive shipping fee; they can also influence customers to purchase other products using a recommendation system. This article provides a combined model in which the shipping-fee discount and product recommendations occur jointly to maximize the sales volume of e-tailers. Selection of recommended products and discount of shipping fee are the dynamic issues involving the complexity of business environments. The proposed model first determines the optimal shipping-fee discount to attract customers and then establishes the most suitable product recommendation list to encourage customers to spend more money on other products. Through the use of a shipping-fee discount and simultaneous product recommendations, e-tailers maximize the sales volume. As for consumers, they can always get additional savings from the subsequent shopping process because the product’s shipping fee is lower than the original shipping costs. Experimental results indicate that the proposed approach is feasible and better than alternative methods for achieving sales volume maximization. Furthermore, sensitivity analysis validates the stability of the proposed model in the face of an uncertain environment. Therefore, using the shipping-fee discount and product recommendation system as a united marketing strategy can maximize e-tailers’ sales volume.